Conditionals in Tuwuli - Matthew Harley (LibraryPress@UF, 2017)
This article examines the forms and functions of conditional clauses in Tuwuli, a Kwa language spoken in South-Eastern Ghana. It reveals how the traditional categories of conditionals (e.g. hypothetical, counterfactual, concessive) do not match up very well with the formal categories found in Tuwuli, and attempts to provide semantic characterisations for each distinct construction. The article also investigates the distribution and functions of conditional clauses in Tuwuli discourse, showing how some text types and genres use conditionals much more than others, and in some cases, for quite distinct purposes.